Marketing automation : practical steps to more effective direct marketing - LeSueur, Jeff, 1956- (Hoboken, N.J. : John Wiley & Sons, 2007)
In today's market, it takes more than good products and services to succeed. Successful marketing requires more precise segmentation and more sophisticated communications with customers--the lifeblood of every business--than ever before. Expertly explaining the components of marketing automation and their application and benefit to the marketing process, Marketing Automation shows you how to develop more effective and targeted direct marketing campaigns, from the planning and execution of promotions to the complete leveraging of marketing to increase your profits. Designed to get you quickly up.
Profit and loss fundamentals -- Profit and loss component details -- Managing the P & L -- Measuring marketing effectiveness -- Measuring return on investment -- Marketing financials -- Improving response : modeling and analytics -- Creating a marketing financials worksheet -- Relevant marketing automation information -- Financial and marketing information integration -- Marketing customer information -- Data acquisition, storage, and retrieval -- Data warehouse hardware and software configuration -- Making information useful : access, delivery, and organization -- Information map -- Using information -- Response testing -- Modeling -- Optimizing contact strategy -- Strategic marketing.
Includes index.
Print version record.
English.
John Wiley and Sons
Keywords: Direct marketing; Marketing -- Data processing; Marketing direct; Marketing -- Informatique; BUSINESS & ECONOMICS -- Marketing -- Telemarketing; BUSINESS & ECONOMICS -- Marketing -- Multilevel; BUSINESS & ECONOMICS -- Mail Order; BUSINESS & ECONOMICS -- Marketing -- Direct; BUSINESS & ECONOMICS -- E-Commerce -- Internet Marketing; Direct marketing; Marketing -- Data processing